A heat-resistant lightweight magnesium alloy and a preparation method thereof

By adding Mn, Sn, Sc and Ce components to the magnesium alloy, aging hardening effect and thermally stable phases are formed, which solves the problems of the decline in strength and insufficient thermal stability of traditional magnesium alloys at high temperatures, and realizes the heat resistance of magnesium alloys Performance improvement and lightweight properties are maintained.

CN115896571BActive Publication Date: 2025-02-07NORTHEASTERN UNIV CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211502120.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-28
Publication Date
2025-02-07
Estimated Expiration
2042-11-28

AI Technical Summary

Technical Problem

Traditional magnesium alloys have decreased strength in high temperature environments, low thermal stability, and the large amount of addition of heavy rare earths or Zn leads to an increase in material density, limiting their application areas.

Method used

By adding four components Mn, Sn, Sc and Ce to the magnesium alloy, a compound with a strong aging hardening effect is formed, and a thermally stable phase is formed by Li and Sn to improve the heat resistance of the magnesium alloy. At the same time, solid-state coating mixing method and variable temperature smelting technology are used to avoid oxidative burning of Li and difficulty in smelting of magnesium alloys.

Benefits of technology

It significantly improves the heat resistance and thermal stability of magnesium alloys, maintains lightweight properties, reduces production costs, and expands the application field of magnesium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115896571B_ABST
    Figure CN115896571B_ABST
Patent Text Reader

Abstract

The present invention provides a heat-resistant light magnesium alloy, which comprises, by mass percentage, 5.0-10.0% Li, 1.0-3.5% Mn, 0.5-2.0% Sn, 0.5-1.5% Sc, 0.5-1.0% Ce, the total amount of impurity elements Si, Fe, and Cu is less than 0.02%, and the balance is Mg. The present invention also provides a method for preparing the heat-resistant light magnesium alloy. The heat-resistant light magnesium alloy provided by the present invention has good thermal stability, and the preparation method of the heat-resistant light magnesium alloy provided by the present invention is simple and easy to operate, and easy to realize mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal materials and metallurgy, and in particular to a heat-resistant lightweight magnesium alloy and a preparation method thereof. Background Art

[0002] Magnesium alloy is the lightest metal structural material to date, with a density of 1.35-1.65g / cm 3 It is the best material to solve the problem of lightweight metal components of satellites in the aerospace field. However, the strength of traditional magnesium alloys is insufficient, significantly lower than that of existing aluminum alloys, making it difficult to directly replace them in load-bearing structural parts. Especially in high temperature environments, the strength of magnesium alloys decreases significantly, and the load-bearing capacity is seriously insufficient. Therefore, developing magnesium alloys with good heat resistance is one of the development directions of magnesium alloys.

[0003] In recent years, a lot of research work has been carried out in the field of magnesium alloy research at home and abroad. The existing Mg-Li alloy materials mainly contain Al, Zn and rare earth elements. The improvement of the strength of magnesium alloys, especially the high-temperature strength, by Al and Zn elements is very limited. Rare earth elements are effective elements for improving the performance of magnesium alloys. The addition of light rare earth elements alone or in combination can improve the performance of magnesium alloys to a certain extent; heavy rare earths improve the performance of magnesium alloys better than light rare earths. In order to improve the heat resistance of magnesium alloys, the current method is mainly to improve the heat resistance of magnesium alloys by adding a large amount of rare earths or by adding a combination of low rare earths and high Zn. However, some of these alloys have low thermal stability and some are prone to aging softening. In addition, the addition of a large amount of heavy rare earths or Zn greatly increases the density of the material. The existence of these problems has greatly affected the full play of the advantages of magnesium alloys and limited their application areas.

[0004] Therefore, it is an urgent problem to develop a heat-resistant magnesium alloy material with good thermal stability, which can be prepared by a preparation method that is simple in process, easy to implement and capable of mass production, so as to expand the application field of magnesium alloy. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a heat-resistant lightweight magnesium alloy with good thermal stability, and to provide a preparation method of the heat-resistant lightweight magnesium alloy which is simple and easy to implement and can be easily mass-produced.

[0006] In order to solve the above technical problems, the present invention provides a heat-resistant lightweight magnesium alloy, which comprises, by mass percentage, 5.0-10.0% Li, 1.0-3.5% Mn, 0.5-2.0% Sn, 0.5-1.5% Sc, 0.5-1.0% Ce, the total amount of impurity elements Si, Fe, and Cu is less than 0.02%, and the balance is Mg.

[0007] The present invention also provides a method for preparing a heat-resistant lightweight magnesium alloy, comprising the following steps:

[0008] In terms of mass percentage, the raw materials are prepared according to the composition of 5.0-10.0% Li, 1.0-3.5% Mn, 0.5-2.0% Sn, 0.5-1.5% Sc, 0.5-1.0% Ce, the total amount of impurity elements Si, Fe, and Cu is less than 0.02%, and the balance is Mg;

[0009] Pure Li is coated with industrial pure Mg ingots and compacted, and then placed in a melting furnace preheated to 200-350°C and kept warm until Li is dissolved and diffused in Mg, and then the melting furnace is heated to 650-750°C and preheated pure Sn, Mg-Mn master alloy, Mg-Sc master alloy and Mg-Ce master alloy are added in sequence, and after all materials are melted, they are stirred and mixed to obtain an alloy melt;

[0010] Refining and degassing the alloy melt;

[0011] The temperature of the melting furnace is controlled at 690-730°C and the alloy melt is kept warm for 30-90 minutes;

[0012] Semi-continuously casting the alloy melt to obtain an ingot;

[0013] The ingot is homogenized and then air-cooled;

[0014] Turning the air-cooled ingot;

[0015] The turned ingot is heated and then extruded into a shape;

[0016] The extruded material is subjected to aging heat treatment and then air-cooled.

[0017] Furthermore, when the industrial pure Mg ingot is used to coat pure Li, the thickness of the Mg ingot must be ensured to avoid being melted through by Li when pure Li is melted.

[0018] Furthermore, the preheated temperatures of the pure Sn, Mg-Mn master alloy, Mg-Sc master alloy and Mg-Ce master alloy are 300-400° C.; the mass percentage of Mn in the Mg-Mn master alloy is 5%, the mass percentage of Sc in the Mg-Sc master alloy is 5%, and the mass percentage of Ce in the Mg-Ce master alloy is 25%.

[0019] Furthermore, the alloy melt refining and degassing treatment adopts an ultrasonically driven flux and inert gas method, the ultrasonic power is 50-4000W, the treatment time is 15-40min, the flux is 500-1000g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 0.5-2.0L / min argon.

[0020] Furthermore, during the semi-continuous casting process of the alloy melt, a phase-difference dual-frequency pulsed magnetic field is used to regulate the flow of the alloy melt, with a phase difference of 60 to 120°, a current of 80 to 180A, a dual-frequency medium and high frequency range of 50 to 200Hz, a low frequency of 10-30Hz, and a pulse duty cycle of 20% to 80%.

[0021] Furthermore, the processing temperature of the ingot homogenization treatment is 280-350° C., and the processing time is 10-18 hours.

[0022] Furthermore, the heating temperature of the ingot after turning is 300-400°C, and the heating of the ingot after turning adopts gradient heating, and the temperature difference between the head and the tail of the ingot is controlled at 40-70°C.

[0023] Furthermore, the ingot is extruded by a reverse extruder, the extrusion speed is 1.0-5.0 m / min, the preheating temperature of the extrusion barrel is 250-350° C., and the extrusion ratio is 10-50:1.

[0024] Furthermore, the aging heat treatment temperature of the extruded material is 150-225° C., and the heat preservation time is 20-50 hours.

[0025] The present invention provides a heat-resistant lightweight magnesium alloy. Four components of Mn, Sn, Sc and Ce are added to the magnesium alloy at the same time, and a compound with a strong aging hardening effect formed by Mn and Sc is introduced into the magnesium alloy matrix. At the same time, the addition of the Sn component can form a large amount of thermally stable phase with Li to strengthen the β-Li matrix, thereby greatly improving the heat resistance of the magnesium alloy.

[0026] In addition, the present invention provides a method for preparing a heat-resistant lightweight magnesium alloy, which uses a solid coating mixing method to complete the mixing of industrial pure Mg and Li before smelting, and then performs low-temperature heating to fully dissolve and diffuse the highly active and low-melting-point Li element into Mg while ensuring that Mg does not melt, thereby avoiding the oxidation and burning of Li. At the same time, the addition of the Ce component can also reduce the oxidation and burning of Mg during high-temperature smelting, thereby greatly reducing the difficulty of smelting magnesium alloys.

[0027] Moreover, the method for preparing a heat-resistant lightweight magnesium alloy provided by the present invention has a simple process, and the equipment used is also conventional general equipment. The production is easy to implement and the production cost is low. It effectively solves the problem of difficulty in preparing magnesium alloys, improves economic benefits, and is conducive to expanding the application field of magnesium alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A flow chart of a method for preparing a heat-resistant lightweight magnesium alloy provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0029] A heat-resistant lightweight magnesium alloy provided in an embodiment of the present invention comprises, by mass percentage, 5.0-10.0% Li, 1.0-3.5% Mn, 0.5-2.0% Sn, 0.5-1.5% Sc, 0.5-1.0% Ce, the total amount of impurity elements Si, Fe, and Cu is less than 0.02%, and the balance is Mg.

[0030] See also Figure 1 The present invention provides a method for preparing a heat-resistant lightweight magnesium alloy, comprising the following steps:

[0031] Step 1) Prepare raw materials according to the composition of 5.0-10.0% Li, 1.0-3.5% Mn, 0.5-2.0% Sn, 0.5-1.5% Sc, 0.5-1.0% Ce, the total amount of impurity elements Si, Fe, Cu is less than 0.02%, and the balance is Mg.

[0032] Step 2) Before smelting, a solid-state coating and compacting method is used to coat pure Li with industrial pure Mg ingots and compact them. Moreover, when coating pure Li with industrial pure Mg ingots, the thickness of the Mg ingots must be ensured to prevent Li from melting through when Li is heated and melted. Then, the Mg ingot coated with pure Li is placed in a smelting furnace preheated to 200-350°C for insulation. After Li is fully dissolved and diffused in Mg, the furnace temperature is raised. When the smelting furnace temperature rises to 650-750°C, pure Sn, Mg-Mn master alloy, Mg-Sc master alloy and Mg-Ce master alloy preheated to 300-400°C are added in sequence. After all materials are melted, they are fully stirred and mixed to obtain an alloy melt. This variable temperature smelting method can avoid the problem of difficulty in smelting low-melting-point Li with other high-melting-point metals.

[0033] The mass percentage of Mn in the Mg-Mn master alloy is 5%, the mass percentage of Sc in the Mg-Sc master alloy is 5%, and the mass percentage of Ce in the Mg-Ce master alloy is 25%.

[0034] Step 3) The alloy melt is subjected to a refining and degassing treatment to reduce the H content in the alloy melt and prevent the formation of hydrides that affect the alloy properties. At the same time, slag inclusions in the alloy melt can be removed, thereby purifying the magnesium alloy melt and improving the metallurgical quality of the melt.

[0035] Among them, the alloy melt refining and degassing treatment adopts an ultrasonically driven flux and inert gas method, the ultrasonic power is 50-4000W, the processing time is 15-40min, the flux is 500-1000g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 0.5-2.0L / min argon.

[0036] Step 4) After the alloy melt is refined and degassed, there are defects such as slag inclusions and / or gas in the just refined alloy melt, as well as problems such as uneven temperature and composition. Therefore, the temperature of the smelting furnace is controlled at 690-730°C to keep the alloy melt warm for 30-90 minutes. By keeping it still at this temperature for a period of time, the slag inclusions and / or gas can be removed by precipitation or floating, thereby improving the metallurgical quality of the alloy melt. If the temperature of the alloy melt is too low, the viscosity of the alloy melt is large, which is not conducive to the removal of defects therein, and it will also cause difficulties in the subsequent casting of the alloy melt ingots. However, if the temperature of the alloy melt is too high, the magnesium alloy melt is easily oxidized and burned, causing secondary pollution. Therefore, the insulation temperature of the alloy melt is controlled at 690-730°C. At the same time, if the insulation time of the corresponding alloy melt is too short, it is not conducive to the removal of defects in the alloy melt. If the insulation time is too long, it is also easy to cause secondary pollution and increase unnecessary smelting costs. Therefore, the insulation time of the alloy melt is controlled within 30-90 minutes.

[0037] Step 5) semi-continuously casting the alloy melt to obtain an ingot. In the semi-continuous casting process of the alloy melt, a phase-difference dual-frequency pulse magnetic field is used to control the flow of the alloy melt, the phase difference is controlled to be 60-120°, the current is 80-180A, the dual-frequency medium and high frequency range is 50-200Hz, the low frequency is 10-30Hz, and the pulse duty cycle is 20%-80%.

[0038] Step 6) homogenizing the ingot obtained by semi-continuous casting and then air cooling the ingot, wherein the processing temperature of the ingot homogenization treatment is controlled at 280-350° C. and the processing time is controlled at 10-18 hours.

[0039] Step 7) Since the ingot obtained by semi-continuous casting has many surface defects, which have a great impact on the quality of subsequent product extrusion, the ingot is air-cooled and turned after homogenization to remove the defective parts on the surface of the ingot.

[0040] Step 8) In order to obtain a product with a desired structure, improve the internal organizational structure of the product, and enhance the performance of the product, the ingot after turning is heated and then extruded.

[0041] The ingot after turning is heated to 300-400°C before extrusion. The ingot after turning is heated by gradient heating, and the temperature difference between the head and the tail of the ingot is controlled at 40-70°C.

[0042] The ingot is extruded by a reverse extruder, the extrusion speed is controlled at 1.0-5.0 m / min, the preheating temperature of the extrusion barrel is 250-350°C, and the extrusion ratio is 10-50:1.

[0043] Step 9) subjecting the extruded material to aging heat treatment and then air cooling, wherein the aging heat treatment temperature of the extruded material is 150-225° C. and the holding time is 20-50 hours.

[0044] The following is a further description of the preparation method of a heat-resistant lightweight magnesium alloy provided by the present invention through an embodiment. It should be understood that the embodiments of the present invention are used to illustrate the present invention rather than to limit the present invention. Simple improvements made to the present invention according to the essence of the present invention all fall within the scope of protection claimed by the present invention.

[0045] In the following embodiments of the present invention, Mg, Li and Sn are added in the form of industrial pure Mg, pure Li and pure Sn, and Mn, Sc and Ce are added in the form of Mg-5% Mn, Mg-5% Sc and Mg-25% Ce master alloys, respectively. That is, the mass percentage of Mn in the Mg-Mn master alloy is 5%, the mass percentage of Sc in the Mg-Sc master alloy is 5%, and the mass percentage of Ce in the Mg-Ce master alloy is 25%.

[0046] Example 1

[0047] The composition (mass percentage) of the alloy is: 5.0% Li, 2.5% Mn, 1.5% Sn, 1.0% Sc, 1.0% Ce, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.

[0048] According to the above ingredients, a total amount of 50 kg of corresponding metal ingots and intermediate alloys are weighed out. Before smelting, pure Li is coated with the prepared industrial pure Mg ingot and compacted, and then placed in a smelting furnace preheated to 250° C. for insulation. After Li is fully dissolved and diffused in Mg, the furnace temperature is raised to 720° C., and the prepared Mg-25% Ce, Mg-5% Mn, Mg-5% Sc intermediate alloys and pure Sn preheated to 300° C. are added in sequence. After all the materials are melted, they are fully stirred and mixed. After the alloy is fully melted, the melt is subjected to ultrasonically driven flux and inert gas refining and degassing treatment, with an ultrasonic power of 500 W and a treatment time of 20 min. The flux is 500 g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 0.5 L / min. After that, the melting furnace is controlled at 700℃ for insulation and standing for 60 minutes, and then semi-continuous casting is carried out. A dual-frequency pulse magnetic field with a phase difference of 90°, a current of 100A, a dual-frequency medium and high frequency range of 50Hz, a low frequency of 30Hz, and a pulse duty cycle range of 40% is used to stir the melt and solidify it to prepare an ingot. The semi-continuously cast ingot is kept at 300℃ for 12 hours, homogenized, air-cooled, and then turned. The ingot after turning is heated to about 350℃, and the temperature difference between the head and the tail of the ingot is ensured to be 50℃. It is extruded by a reverse extruder at an extrusion speed of 2.0m / min, an extrusion barrel temperature of 300℃, and an extrusion ratio of 20:1; the extruded material is kept at 150℃ for 35 hours for aging treatment.

[0049] The material prepared by the above process was processed into a standard tensile specimen according to the national standard GB / T228-2010, and the tensile property test was carried out on an Instron 8032 tensile machine.

[0050] The tensile properties of the alloy obtained in this embodiment are as follows: the tensile strength at room temperature is 347 MPa, the yield strength is 229 MPa, and the elongation is 19.5%; the tensile strength at 200°C is 173 MPa, the yield strength is 119 MPa, and the elongation is 47%.

[0051] Example 2

[0052] The composition (mass percentage) of the alloy is: 7.0% Li, 1.0% Mn, 1.0% Sn, 0.5% Sc, 0.3% Ce, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.

[0053] According to the above ingredients, a total of 80 kg of corresponding metal ingots and intermediate alloys are weighed out. Before smelting, pure Li is coated with the prepared industrial pure Mg ingot and compacted, and then placed in a smelting furnace preheated to 300° C. for insulation. After Li is fully dissolved and diffused in Mg, the furnace temperature is raised to 700° C., and the prepared Mg-25% Ce, Mg-5% Mn, Mg-5% Sc intermediate alloys and pure Sn preheated to 400° C. are added in sequence. After all the materials are melted, they are fully stirred and mixed. After the alloy is fully melted, the melt is subjected to ultrasonically driven flux and inert gas refining and degassing treatment, with an ultrasonic power of 1000 W and a treatment time of 30 min. The flux is 600 g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 1.0 L / min. After that, the melting furnace is controlled at 700℃ for insulation and standing for 50 minutes, and then semi-continuous casting is carried out. A dual-frequency pulse magnetic field with a phase difference of 90°, a current of 130A, a dual-frequency medium and high frequency range of 50Hz, a low frequency of 25Hz, and a pulse duty cycle range of 50% is used to stir the melt and solidify it to prepare an ingot. The semi-continuously cast ingot is kept at 280℃ for 15 hours, homogenized, air-cooled, and then turned. The ingot after turning is heated to about 350℃, and the temperature difference between the head and tail of the ingot is ensured to be 40℃. It is extruded by a reverse extruder at an extrusion speed of 2.0m / min, an extrusion barrel temperature of 300℃, and an extrusion ratio of 17:1; the extruded material is kept at 170℃ for 30 hours for aging treatment.

[0054] The material prepared by the above process was processed into a standard tensile specimen according to the national standard GB / T228-2010, and the tensile property test was carried out on an Instron 8032 tensile machine.

[0055] The tensile properties of the alloy obtained in this embodiment are: tensile tensile strength is 323MPa, yield strength is 214MPa, and elongation is 23% under room temperature conditions; tensile tensile strength is 157MPa, yield strength is 103MPa, and elongation is 54% under 200°C conditions.

[0056] Example 3

[0057] The composition (mass percentage) of the alloy is: 9.0% Li, 2.0% Mn, 1.0% Sn, 0.6% Sc, 0.5% Ce, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.

[0058] According to the above ingredients, a total of 30 kg of corresponding metal ingots and intermediate alloys are weighed out. Before smelting, pure Li is coated with the prepared industrial pure Mg ingot and compacted, and then placed in a smelting furnace preheated to 280° C. for insulation. After Li is fully dissolved and diffused in Mg, the furnace temperature is raised to 710° C., and the prepared Mg-25% Ce, Mg-5% Mn, Mg-5% Sc intermediate alloys preheated to 350° C. and pure Sn are added in sequence. After all the materials are melted, they are fully stirred and mixed. After the alloy is fully melted, the melt is subjected to ultrasonically driven flux and inert gas refining and degassing treatment, with an ultrasonic power of 400 W and a treatment time of 15 min. The flux is 400 g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 0.5 L / min. After that, the melting furnace is controlled at 690℃ for insulation and standing for 30 minutes, and then semi-continuous casting is carried out. A dual-frequency pulse magnetic field with a phase difference of 100°, a current of 80A, a dual-frequency medium and high frequency range of 80Hz, a low frequency of 30Hz, and a pulse duty cycle range of 80% is used to stir the melt and solidify it to prepare an ingot. The semi-continuously cast ingot is kept at 280℃ for 15h, homogenized, air-cooled, and then turned. The ingot after turning is heated to about 340℃, and the temperature difference between the head and tail of the ingot is ensured to be 30℃. It is extruded by a reverse extruder at an extrusion speed of 1.8m / min, an extrusion barrel temperature of 330℃, and an extrusion ratio of 25:1; the extruded material is kept at 200℃ for 20h for aging treatment.

[0059] The material prepared by the above process was processed into a standard tensile specimen according to the national standard GB / T228-2010, and the tensile property test was carried out on an Instron 8032 tensile machine.

[0060] The tensile properties of the alloy obtained in this embodiment are as follows: the tensile strength at room temperature is 336 MPa, the yield strength is 221 MPa, and the elongation is 26%; the tensile strength at 200°C is 161 MPa, the yield strength is 110 MPa, and the elongation is 49%.

[0061] Example 4

[0062] The composition (mass percentage) of the alloy is: 5.0% Li, 1.5% Mn, 0.5% Sn, 0.3% Sc, 0.3% Ce, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.

[0063] According to the above ingredients, a total of 80 kg of corresponding metal ingots and intermediate alloys are weighed out. Before smelting, pure Li is coated with the prepared industrial pure Mg ingot and compacted, and then placed in a smelting furnace preheated to 320° C. for insulation. After Li is fully dissolved and diffused in Mg, the furnace temperature is raised to 710° C., and the prepared Mg-25% Ce, Mg-5% Mn, Mg-5% Sc intermediate alloys and pure Sn preheated to 300° C. are added in sequence. After all the materials are melted, they are fully stirred and mixed. After the alloy is fully melted, the melt is subjected to ultrasonically driven flux and inert gas refining and degassing treatment, with an ultrasonic power of 2000 W and a treatment time of 40 min. The flux is 700 g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 1.5 L / min. After that, the melting furnace was controlled at 720℃ for insulation and allowed to stand for 80 minutes, and then semi-continuous casting was carried out. A dual-frequency pulse magnetic field with a phase difference of 90°, a current of 140A, a dual-frequency medium and high frequency range of 90Hz, a low frequency of 25Hz, and a pulse duty cycle range of 60% was used to stir the melt and solidify it to prepare an ingot. The semi-continuously cast ingot was kept at 310℃ for 15 hours, homogenized, air-cooled, and then turned. The ingot after turning was heated to about 300℃, and the temperature difference between the head and tail of the ingot was ensured to be 40℃. It was extruded by a reverse extruder at an extrusion speed of 1.5m / min, an extrusion barrel temperature of 300℃, and an extrusion ratio of 20:1; the extruded material was kept at 160℃ for 33 hours for aging treatment.

[0064] The material prepared by the above process was processed into a standard tensile specimen according to the national standard GB / T228-2010, and the tensile property test was carried out on an Instron 8032 tensile machine.

[0065] The tensile properties of the alloy obtained in this embodiment are: tensile tensile strength is 320MPa, yield strength is 217MPa, and elongation is 21% under room temperature conditions; tensile tensile strength is 155MPa, yield strength is 114MPa, and elongation is 53% under 200°C conditions.

[0066] Example 5

[0067] The composition (mass percentage) of the alloy is: 10.0% Li, 3.0% Mn, 2.0% Sn, 1.3% Sc, 1.0% Ce, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.

[0068] According to the above ingredients, a total of 20 kg of corresponding metal ingots and intermediate alloys are weighed out. Before smelting, pure Li is coated with the prepared industrial pure Mg ingot and compacted, and then placed in a smelting furnace preheated to 290° C. for insulation. After Li is fully dissolved and diffused in Mg, the furnace temperature is raised to 690° C. and then the prepared Mg-25% Ce, Mg-5% Mn, Mg-5% Sc intermediate alloys and pure Sn preheated to 400° C. are added in sequence. After all the materials are melted, they are fully stirred and mixed. After the alloy is fully melted, the melt is subjected to ultrasonically driven flux and inert gas refining and degassing treatment, the ultrasonic power is 700 W, the treatment time is 30 min, the flux is 500 g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 0.5 L / min. After that, the melting furnace is controlled at 730℃ for insulation and standing for 40 minutes, and then semi-continuous casting is carried out. A dual-frequency pulse magnetic field with a phase difference of 120°, a current of 80A, a dual-frequency medium and high frequency range of 100Hz, a low frequency of 20Hz, and a pulse duty cycle range of 70% is used to stir the melt and solidify it to prepare an ingot. The semi-continuously cast ingot is kept at 310℃ for 9 hours, homogenized, air-cooled, and then turned. The ingot after turning is heated to about 340℃, and the temperature difference between the head and tail of the ingot is ensured to be 40℃. It is extruded by a reverse extruder at an extrusion speed of 1.0m / min, an extrusion barrel temperature of 300℃, and an extrusion ratio of 40:1; the extruded material is kept at 200℃ for 20 hours for aging treatment.

[0069] The material prepared by the above process was processed into a standard tensile specimen according to the national standard GB / T228-2010, and the tensile property test was carried out on an Instron 8032 tensile machine.

[0070] The tensile properties of the alloy obtained in this embodiment are: tensile tensile strength is 331 MPa, yield strength is 215 MPa, and elongation is 24% under room temperature conditions; tensile tensile strength is 161 MPa, yield strength is 122 MPa, and elongation is 58% under 200°C conditions.

[0071] It can be seen from the above embodiments that the method for preparing a heat-resistant lightweight magnesium alloy provided by the present invention, the lightweight magnesium alloy prepared not only has high strength at room temperature, but also has high strength under high temperature conditions of 200°C, which can be explained that the magnesium alloy prepared by the present invention has good heat resistance.

[0072] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a heat-resistant lightweight magnesium alloy, characterized in that: The steps include: The raw materials are prepared in a composition ratio of 5.0-10.0% Li, 1.0-3.5% Mn, 0.5-2.0% Sn, 0.5-1.5% Sc, 0.5-1.0% Ce, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and the balance is Mg; Pure Li is coated with industrial pure Mg ingots and compacted, and then placed in a melting furnace preheated to 200-350°C and kept warm until Li is dissolved and diffused in Mg, and then the melting furnace is heated to 650-750°C and preheated pure Sn, Mg-Mn master alloy, Mg-Sc master alloy and Mg-Ce master alloy are added in sequence, and after all materials are melted, they are stirred and mixed to obtain an alloy melt; Refining and degassing the alloy melt; The temperature of the melting furnace is controlled at 690-730°C and the alloy melt is kept warm for 30-90 minutes; Semi-continuously casting the alloy melt to obtain an ingot; The ingot is homogenized and then air-cooled; Turning the air-cooled ingot; The turned ingot is heated and then extruded into a shape; The extruded material is subjected to aging heat treatment and then air-cooled.

2. The method for preparing a heat-resistant lightweight magnesium alloy according to claim 1, characterized in that: When the industrial pure Mg ingot is used to coat pure Li, the thickness of the Mg ingot must be ensured to avoid being melted through by Li when pure Li is melted.

3. The method for preparing a heat-resistant lightweight magnesium alloy according to claim 1, characterized in that: The preheated temperatures of the pure Sn, Mg-Mn master alloy, Mg-Sc master alloy and Mg-Ce master alloy are 300-400° C. The mass percentage of Mn in the Mg-Mn master alloy is 5%, the mass percentage of Sc in the Mg-Sc master alloy is 5%, and the mass percentage of Ce in the Mg-Ce master alloy is 25%.

4. The method for preparing a heat-resistant lightweight magnesium alloy according to claim 1, characterized in that: The alloy melt refining and degassing treatment adopts an ultrasonically driven flux and inert gas method, the ultrasonic power is 50-4000W, the treatment time is 15-40min, the flux is 500-1000g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 0.5-2.0L / min of argon.

5. The method for preparing a heat-resistant lightweight magnesium alloy according to claim 1, characterized in that: During the semi-continuous casting process of the alloy melt, a phase-difference dual-frequency pulse magnetic field is used to control the flow of the alloy melt, the phase difference is 60-120°, the current is 80-180A, the dual-frequency medium and high frequency range is 50-200Hz, the low frequency is 10-30Hz, and the pulse duty cycle is 20%-80%.

6. The method for preparing a heat-resistant lightweight magnesium alloy according to claim 1, characterized in that: The processing temperature of the ingot homogenization treatment is 280-350° C., and the processing time is 10-18 hours.

7. The method for preparing a heat-resistant lightweight magnesium alloy according to claim 1, characterized in that: The heating temperature of the ingot after turning is 300-400°C, and the heating of the ingot after turning adopts gradient heating, and the temperature difference between the head and the tail of the ingot is controlled at 40-70°C.

8. The method for preparing a heat-resistant lightweight magnesium alloy according to claim 1, characterized in that: The ingot is extruded by a reverse extruder, the extrusion speed is 1.0-5.0 m / min, the preheating temperature of the extrusion barrel is 250-350° C., and the extrusion ratio is 10-50:

1.

9. The method for preparing a heat-resistant lightweight magnesium alloy according to claim 1, characterized in that: The aging heat treatment temperature of the extruded material is 150-225° C., and the temperature is kept for 20-50 hours.

Citation Information

Patent Citations

  • Multicomponent heat resisting magnesium alloy and preparation thereof

    CN101440449A

  • Sn-containing fine-grained magnesium-lithium tin alloy

    CN102031432A

  • Multi-element microalloyed biphase magnesium-lithium alloy and preparation method thereof

    CN110029254A

  • Cold press forming method for magnesium alloy

    JP2003226929A